Design and implementation of microstrip rotman lens for ISM band applications - Mohammed K. Al-Obaidi; Ezri Mohd; Noorsaliza Abdullah; Samsul Haimi Dahlan; Jawad Ali (Bulletin of Electrical Engineering and Informatics, 2019)
This work presents the design and implementation of Rotman lens as a beam steering device for Industrial, Scientific, and Medical (ISM) applications. 2.45 GHz is considered as a center frequency design with (2-6) GHz frequency bandwidth. The beam steering is examined to cover ±21o scan angle with maximum main lobe magnitude 10.1 dBi, rectangular patch antennas are used as radiation elements to beam the output far field. The work is extended to compare between the tapered line which is used for matching between 50-Ω ports and lens cavity. CST microwave simulation studio results show that the rectangular taper line can yield 2 dB return loss less than linear taper line with a little bit shifting in responses for same input and load impedance.